1999
DOI: 10.1046/j.1462-5822.1999.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Signalling and cellular specificity of airway nitric oxide production in pertussis

Abstract: SummaryBordetella pertussis, the aetiological agent of whooping cough (pertussis), causes selective destruction of ciliated cells of the human airway mucosa. In a hamster tracheal organ culture model, B. pertussis causes identical cytopathology as does tracheal cytotoxin (TCT), a glycopeptide released by the bacterium. The damage caused by B. pertussis or TCT has been shown to be mediated via nitric oxide (NO?). Using immuno¯uorescence detection of the cytokine-inducible NO synthase (iNOS; NOS type II), we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
6

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 24 publications
2
55
0
6
Order By: Relevance
“…Contrary evidence, presented by Flak and Goldman (8), indicated that B. pertussis endotoxin plays a crucial role in the selective destruction of the ciliated cells of human airway mucosa. In this process the endotoxin works synergistically with tracheal cytotoxin by inducing a toxic level of NO released from secretory epithelial cells.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Contrary evidence, presented by Flak and Goldman (8), indicated that B. pertussis endotoxin plays a crucial role in the selective destruction of the ciliated cells of human airway mucosa. In this process the endotoxin works synergistically with tracheal cytotoxin by inducing a toxic level of NO released from secretory epithelial cells.…”
Section: Discussionmentioning
confidence: 81%
“…It has been shown that LOS of B. pertussis is an antigen in natural infection (44), and new findings suggest that it is an important etiological factor in whooping cough pathogenesis and is directly involved in destruction of the ciliated cells of the human airways mucosa (8). LOS, working synergistically with tracheal cytotoxin, takes part in induction of nitric oxide synthase in nonciliated epithelial cells, and this is followed by NO release and subsequent damage to the ciliated cells (8,9).…”
Section: B Pertussis Produces Only Two Types Of Lpsmentioning
confidence: 99%
“…The concept of synergy between multiple bacterial cell surface or secreted factors in exerting a proinflammatory effect is well established (5). This concept and the known activities of LPS guided our comparison of FHA with LPS in the assessment of these host cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…NO F then diffuses to neighboring ciliated cells, which are much more susceptible to its damaging effects (250). TCT also functions synergistically with Bordetella LPS to induce the production of NO F within the airway epithelium (251). The ability to construct TCT-deficient mutants by expressing a heterologous ampG gene in Bordetella will allow this hypothesis to be tested by using in vivo models.…”
Section: Virulence Determinantsmentioning
confidence: 99%